Studies on Variations in Textured Grain Growth in ZnO Nano Thin Films by Aluminium and Iodine Doping - Thomas1, Deepu; C. Vattappalam2, Sunil; Mathew2, Sunny; Augustine2, Simon (Asian Journal of Chemistry, 2013)
ZnO thin films were prepared by successive ionic layer adsorption reaction (SILAR) method. The variations in the textured grain growth along c-axis in the aluminium doped and iodine doped thin films were studied. Textured grain growth of the samples was measured by using an orientation index (O.I.), which is the ratio of the intensities of (002) reflection (2q = 34º) to (101) reflection (2q = 36º) in the XRD patterns. From the studies following conclusions were drawn. Textured grain growth in ZnO thin films is enhanced by aluminium and iodine doping. When the oriented grain growth increases, crystallinity of the thin film improves, resistance and band gap decreases. A possible mechanism for the textured grain growth is also investigated. It is inferred that the creation of defects are responsible for the enhanced textured grain growth in ZnO thin films by aluminium and iodine doping.